DESAIN KURIKULUM PENDIDIKAN ISLAM BERBASIS EKOTEOLOGI: INTREGASI NILAI TAUHID DAN KESADARAN LINGKUNGAN - Nor Rochmatul Wachidah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
The global environmental crisis, marked by ecosystem degradation, climate change, and the exploitation of natural resources, reflects a fundamental problem in human moral and spiritual consciousness. In the Islamic perspective, environmental destruction is understood as a reflection of a crisis of faith, so Islamic education holds a strategic role in instilling ecological awareness based on the value of tauhid (divine unity). This study aims to examine the design of an Islamic education curriculum grounded in ecotheology through the integration of tauhid values and environmental awareness in the learning process. The method used is library research involving various literature sources such as books, scientific journals, and other relevant documents. Data analysis was carried out through content analysis to identify concepts, values, and strategies for integrating ecotheology into the Islamic education curriculum. The results indicate that Islamic education based on ecotheology positions humans as khalifah fil ardh (stewards on earth) who bear moral and spiritual responsibility for preserving nature. The integration of tauhid values into the curriculum can shape students’ attitudes and behaviour to be environmentally conscious and to view environmental preservation as part of worship. However, the implementation of this curriculum still faces obstacles, including limited understanding among educators, a lack of contextual teaching materials, and a learning culture that tends to be merely normative. Therefore, the development of an Islamic education curriculum based on ecotheology is needed as a strategic effort to build students’ ecological character in a sustainable manner.